On maps: continuous, closed, perfect, and with closed graph - G. L. Garg; Asha Goel (International Journal of Mathematics and Mathematical Sciences)
This paper gives relationships between continuous maps, closed maps, perfect maps, and maps with closed graph in certain classes of topological spaces.